Compulsive Internet use and workaholism: An exploratory two-wave longitudinal study. (July 2016) - Quinones, Cristina; Griffiths, Mark D.; Kakabadse, Nada K.
Abstract: Workaholism refers to the uncontrollable need to work and comprises working compulsively (WC) and working excessively (WE). Compulsive Internet Use (CIU), involves a similar behavioural pattern although in specific relation to Internet use. Since many occupations rely upon use of the Internet, and the lines between home and the workplace have become increasingly blurred, a self-reinforcing pattern of workaholism and CIU could develop from those vulnerable to one or the other. The present study explored the relationship between these compulsive behaviours utilizing a two-wave longitudinal study over six months. A total of 244 participants who used the Internet as part of their occupational role and were in full-time employment completed the online survey at each wave. This survey contained previously validated measures of each variable. Data were analysed using cross-lagged analysis. Results indicated that Internet usage and CIU were reciprocally related, supporting the existence of tolerance in CIU. It was also found that CIU at Time 1 predicted WC at Time 2 and that WE was unrelated to CIU. It is concluded that a masking mechanism appears a sensible explanation for the findings. Although further studies are needed, these findings encourage a more holistic evaluation and treatment of compulsive behaviours. Highlights: A total of 244 of British adults completed questionnaires at 2 waves over 6 months. Compulsive Internet use predicted working compulsively at Time 2 but not vice-versa. Hours of use and compulsive Internet use were reciprocally related. Working excessively was unrelated to compulsive Internet use. A masking mechanism may explain the association between CIU and working compulsively.